The impact of Pakistan Poverty Alleviation Fund on poverty in Pakistan: an empirical analysis - Yusuf, Muhammad-Bashir; Shirazi, Nasim Shah; Mat Ghani, Gairuzazmi (IDOSI Publications, 2013)
This paper examines the impact of the Pakistani Poverty Alleviation Fund (PPAF) on poverty by using PPAF (2005) data. The analysis was conducted in two stages. The first stage determined the factors influencing access to PPAF microfinance and the second stage examined the impact of PPAF on poverty. Access study was conducted using the logit model. The full model containing all the predictor was statistically significant, indicating that the model was able to distinguish between respondents who have access and those who do not have. The second stage was divided into two steps. The first step examined the difference in the income between PPAF recipients and non recipients. The two incomes were found to be statistically significant but with little effect. The second step used logit model to determine the impact of credit on the poverty status of the beneficiaries. It was found that microcredit has no significant effect on poverty status of the beneficiaries, however six of the factors specified in the model were found to be significant with the model explaining 25 to 35 percent of the factors that determine the poverty status of the respondents.